Photocatalytic Nanocomposites for Amoxicillin Degradation: Mechanistic Insights, Kinetics, and Environmental Implications - Vijayalakshmi , Pandurangan; Thangavelu, Lakshmi; Kandhaswamy , Anandhi; Shahwan, Moyad; Thiruvengadam, Rekha; Thiruvengadam , Muthu; Haque, Mainul (Bangladesh Journal of Medical Science, 2025)
This review comprehensively examines current progress in developing emerging photocatalytic nanocomposites for the degradation of amoxicillin (AMX) in wastewater treatment systems. A range of advanced nanomaterials, including mesoporous carbon nitride (MCN), TiO2 nanoparticles, sulfur-doped C3N5/DyFeO3, and BiVO4, have demonstrated enhanced photocatalytic activity underneath visible light, primarily through the generation for reactive species such as hydroxyl as well as sulfate radicals. Special attention is given to innovative modification strategies, like heterojunction formation, elemental doping, and green synthesis routes that significantly improve photocatalytic efficiency and pollutant selectivity. Notably, MXenebased nanocomposites have achieved AMX removal efficiencies approaching 99%. The review delves into the superior photocatalytic mechanisms underlying these materials, including S-scheme heterojunctions and hybrid configurations like Cs3PMo12O40/MnIn2S4, contributing to enhanced charge separation and interfacial charge transfer. Emerging systems such as α-Fe2O3/WO3/activated carbon and Co3O4/CdO/clinoptilolite are also highlighted for their promising degradation performance under optimized kinetic conditions. Furthermore, the integration of advanced oxidation processes (AOPs) containing UV/chloramine and ozonation is discussed for their synergistic potential in reducing AMX toxicity and improving degradation rates. Complementary biological approaches, including Trametes versicolor fungi, are explored as eco-friendly alternatives for pharmaceutical wastewater remediation. This review provides critical insights into the mechanisms, kinetic optimization strategies, and ecological considerations associated with nanocompositebased photocatalysis. Additionally, it outlines current challenges and forthcoming research directions to advance sustainable and efficient technologies for antibiotic-contaminated wastewater treatment. BJMS, Vol. 24 No. 03 July’25 Page : 709-730